Organised crime in European businesses - Savona, Ernesto Ugo; Riccardi, Michele; Berlusconi, Giulia (Routledge studies in crime and society, 2016)
Introduction / Ernesto U. Savona -- Organised criminals and the legal economy / Giulia Berlusconi -- Measuring organised crime infiltration in legal businesses / Michele Riccardi and Giulia Berlusconi PART I: INFILTRATING LEGITIMATE BUSINESSES TO CONCEAL AND FACILITATE ILLICIT TRAFFICKING -- Transportation companies to hide transit crimes : organised crime infiltration in the Netherlands / Joras Ferwerda and Brigitte Unger -- The sex market, bars and nightclubs : criminal infiltration in Slovenia / Botjan Slak, Maja Modic, Katja Eman and Branko Aman -- From drug trafficking to wholesale trade busines :. organised crime infiltration in Spain / Jesús Palomo, Jerónimo Márquez and Pilar Laguna -- Infiltrating legitimate businesses to develop fraud schemes -- Social welfare fraud and criminal infiltration in Sweden / Johanna Skinnari, Lars Korsell and Helena Rönnblom -- Crash-for-cash and vat carousels : organised crime infiltration in the United Kingdom / David Wall, Yulia Chistyakova and Stefano Bonino -- Infiltrating legitimate businesses to control the territory and influence policy makers -- Mafia infiltration in legitimate companies in Italy : from traditional sectors to emerging businesses / Michele Riccardi, Cristina Soriani and Valentina Giampietri -- Grand banditisme traditionnel and foreign groups : organised crime infiltration in France / Michele Riccardi and Diana Camerini -- From bikers to entrepreneurs : motorcycle gangs infiltration in Finland / Sarianna Petrell and Jarmo Houtsonen -- Research and policy implications -- The impact of organised crime infiltration on the European legitimate economy / John Walker -- From the analysis of criminal infiltration to the assessment of its risk / Lorella Garofalo Conclusions / Ernesto U. Savona